Genetic diversity of Mycobacterium avium sp. Paratuberculosis by mycobacterial interspersed repetitive unit–variable number tandem repeat and multi‑locus short‑sequence repeat one‑sentence summary : genetic diversity of Mycobacterium avium sp. Paratuberculosis isolates - Moyano, Roberto Damián; Imperiale, Belen Rocio; Romero, Magalí; Santangelo, María De La Paz; Alvarado Pinedo, Maria Fiorella; Travería, Gabriel; Romano, Maria Isabel (Wolters Kluwer Medknow, 2021)
Background: Paratuberculosis is an enteric disease caused by Mycobacterium avium sp. paratuberculosis (MAP) that affects mainly ruminant producing losses to the livestock industry. Many molecular epidemiological methods have been used to discriminate MAP isolates. Method: The aim of this study was to describe the genetic diversity of the Argentinean MAP isolates using a combination of two molecular systems, the mycobacterial interspersed repetitive unit–variable number tandem repeat (MIRU-VNTR) (“automated and “non-automated”) and the multi-locus short-sequence repeat (MLSSR) system. Results: Thirty-two isolates were identified as MAP of C type by IS900 polymerase chain reaction (PCA) and IS1311 PCA-restriction enzyme analysis. The main patterns found by both MIRU-VNTR systems were INMV1 (54.5%), INMV2 (24.2%) and INMV11 (9.1%). The INMV5, INMV8 and INMV16 were represented with one isolate each (3.0%). Only 4 MIRU-VNTR loci were polymorphic. Conclusion: Those isolates sharing the same INMV patterns were analyzed by MLSSR, being locus 2 the most polymorphic one showing isolates with 9, 10, 11, and more than 11 “G” repeats. Besides, the global discriminatory power among isolates could be increased using both techniques. Based on these results, a short version of the “automated” MIRU-VNTR could be used as a screening tool to group isolates genetically related and subsequently perform the SSR using locus 2 on those isolates sharing the same INMV pattern.